Self-repair of actions in German: a case for embedded - Lemon, Christopher Shandon (Kansas State University, 2011)
Using conversation analytic methodology, this paper examines the self-repair of actions in everyday German conversation, with focus given to the replacement of verbs and the subsequent effect on actions. While study has been done on the function of recycling repair within a turn (Fox, Hayashi, Jesperson, 1996) no research has been done on the function of verb replacement and its effect on talk. This paper shows that verb replacement is a strategy employed by speakers in order to either a) negotiate what type of action is preferred within a particular TCU or b) to invoke external forces to either deflect an action, or to make a particular action available to an interlocutor. This paper concludes by discussing the specific function of this particular type of repair and how it is useful in repairing problematic actions.
Keywords: Conversation anaysis; Self-repair; CA; Actions; German; Embedded repair; Language, Linguistics (0290)